Injection molding of nickel based 625 superalloy: Sintering, heat treatment, microstructure and mechanical properties - GÜLSOY, HAMİT ÖZKAN (ELSEVIER SCIENCE SA, 2013)
This study concerns determination of optimum sintering and thermal process parameters for Ni-based alloy 625 superalloy formed by the method of powder injection molding (PIM). Samples, formed from the feedstock by mixing the prealloyed 625 powder with a multi-component binding system, are made subject to sintering at different temperatures following the debinding process. Samples that are sintered under such conditions giving way to the highest relative density (3 h at 1300 degrees C), are aged after they have been subject to solution treated thermal process. Sintered, solution treated and aged samples have been subjected to microstructural analysis and mechanical test. Mechanical tests such as hardness measurement and tensile test as well as microstructural characterization such as X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM) and elemental analysis all have shown that the aging thermal process increases strength of the material. However, it is observed that alloy 625 produced by the method of PIM is at such level to compete with the characteristics of cast alloy 625. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Powder injection molding; 625 Superalloy; Sintering; Microstructure; NI-BASED SUPERALLOYS; INCONEL-718 ALLOY; POWDER; PRECIPITATION; EVOLUTION